2014
DOI: 10.1186/s13075-014-0501-5
|View full text |Cite
|
Sign up to set email alerts
|

Anti-tumor necrosis factor patent expiration and the risks of biocopies in clinical practice

Abstract: Biosimilars that were not compared in clinical trials with the compound innovator are not true biosimilars (biocopies) and are associated with risks that the clinical rheumatologist should be aware of before generalized use. This article comments on various aspects surrounding the use of such biocopies in clinical rheumatology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 15 publications
0
22
0
Order By: Relevance
“…Biomimics may differ from originator biologics in their primary structure, dosage, and formulation, which may result in clinically significant differences in efficacy or safety, with the potential to compromise patient care [38]. In Mexico, where biomimics are marketed, there has been automatic substitution by pharmacies of etanercept and rituximab biomimics for the originator products [39]. The lack of adequate post-marketing surveillance programs in some countries, where biomimics are substituted for originator biopharmaceuticasls in an unregulated manner, puts patients at risk for adverse outcomes.…”
Section: A Naming Convention Should Be Implemented To Clearlymentioning
confidence: 99%
“…Biomimics may differ from originator biologics in their primary structure, dosage, and formulation, which may result in clinically significant differences in efficacy or safety, with the potential to compromise patient care [38]. In Mexico, where biomimics are marketed, there has been automatic substitution by pharmacies of etanercept and rituximab biomimics for the originator products [39]. The lack of adequate post-marketing surveillance programs in some countries, where biomimics are substituted for originator biopharmaceuticasls in an unregulated manner, puts patients at risk for adverse outcomes.…”
Section: A Naming Convention Should Be Implemented To Clearlymentioning
confidence: 99%
“…With the recent expiration of patents around the world protecting numerous high‐cost, branded biologic drugs, biosimilars have been developed and introduced in several countries, offering competition and reduced prices . In South Korea, we found that utilization of a newly introduced biosimilar infliximab agent comprised one‐fifth of all infliximab prescription claims within 15 months after its introduction.…”
Section: Discussionmentioning
confidence: 92%
“…2,16,44,57 A 2016 systematic literature review found that most comparative studies reported for such intended copies were either analytical, non-clinical, or observational in nature; as such, there remains a significant dearth of published data demonstrating the safety and efficacy of these agents. 16 …”
Section: Biosimilars In Latin America: Current Situationmentioning
confidence: 99%
“…45 Indeed, suboptimal surveillance processes and systems reportedly contributed to delays in the withdrawal of Kikuzubam®. 2 …”
Section: Biosimilars In Latin America: Current Situationmentioning
confidence: 99%
See 1 more Smart Citation